The fixed point property of unital abelian banach algebras - Fupinwong W. (2017)
We give a general condition for infinite dimensional unital Abelian Banach algebras to fail the fixed point property. Examples of those algebras are given including the algebras of continuous functions on compact sets. Copyright © 2010 W. Fupinwong and S. Dhompongsa.